Post-traumatic cystic lesion following radius fracture: a case report and literature review - Samaila, Elena Manuela; Ditta, Alessandro; Lugani, Giovanni; Regis, Dario; Leigheb, Massimiliano; Leigheb, Massimiliano; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Background: Post-traumatic osseous cystic lesions represent a rare complication in children. Usually a post-fracture cyst is a lipid inclusion cyst, which is radiolucent and may be seen adjacent to a healing torus fracture. It is typically asymptomatic and appears just proximal to the fracture line within the area of subperiosteal new bone formation. Case report: We report a case of post-fracture cyst of the distal radius in an 8 year-old girl with spontaneous resolution. A fat-fluid level within the subperiosteal cystic lesion in MRI is a typical feature of post-traumatic cystic lesion in children. Discussion and conclusion: MRI or CT scan is sufficient to confirm the diagnosis of post-traumatic cystic lesions without the need for further management other than reassurance and advise that they may occasionally cause discomfort but resolve with time.